Proposta de implantação do plano de gerenciamento de resíduos sólidos para uma rede de supermercados, de acordo com as diretrizes da lei nº 12.305/2010 - Debastiani, Solange Maria (2016)
The aim of this dissertation was characterize a Plan of Solid Waste Management (PGRS) for a supermarket chain, according to the guidelines of the Law nº 12.305/2010, including all steps for its implementation, in order to adapt the enterprise to the current legislation. It is a case study, configured as an applied research, which used the exploratory and descriptive methods, with qualitative approach. With regard to data collection procedures, were used, in addition to bibliographic search, raising the organization's records, semi-structured interviews with managers and coordinators of the sectors, direct observation and participatory action research. For data analysis, it was used the content analysis. So, is justified the present study because of business is part of the list of companies considered large waste generators, and according to the requirement of Law nº 12.305/2010, it has the obligation to develop and implement a PGRS. Thus, after the analysis of the data and the identification of improvement points, it can be presented as a contribution to the practice: the elaboration of the PGRS and the action s plans for the implementation of the suggested proposal, in addition to the action research approach. It is expected, with this proposal, which, when deploying the PGRS, the enterprise contemplates not only the legal requirements, but also the environmental, social and financial benefits for the organization, seeking, in this way, that the company becomes environmentally friendly